The Classical Interlude: A Law of Recessive Tonal Accent for ‘Classical’-era Indo-European - David, A. P. (Dramaturgias, 2017)
It is shown that W. S. Allen’s theory of a ‘contonation’, derived from Vedic descriptions, accounts for the apparently divergent ‘tone’ and ‘stress’ rules (respectively) for ancient Greek and Latin, as well as, by extension, classical Sanskrit. Historically, Greek and Latin show evidence of an active stress component in their accentuation in the weakening grade of adjacent vowels, an effect that appears not to be present during the classical period. It turns out that all three classical languages display patterns of accentuation in their received grammatical traditions which can be formulated in terms of a ’recessive’ rule when the role of quantity is factored in.